Autópsia espiritual: análise de narrativas psicofonadas de espíritos suicidas - Gonçalves, Iracilda Cavalcante de Freitas (2019)
Suicide is a complex phenomenon, recently pointed out by the World Health Organization (WHO) as a public health problem that can be prevented. In order to contribute to the understanding of this problem, we decided to "listen” to the voice of the suicidal spirits. Therefore, we first assume that the discourse of the suicidal spirit includes a specific knowledge about the phenomenon of suicide; A saying that for its susceptibility to the listening can be used as a subsidy in the production of preventive actions and the postvention as well. In this matter, this research aims to observe the treatment given by the suicidal spirits to the suicide and suicidal discursive objects. In this research, eleven (11) reports of suicidal spirits were analyzed. The narratives, produced through the psychophonia mediumship, took place in the premises of the Núcleo Espírita Mensageiros do Bem (NEMB), during meetings held by the Core of Studies, Prevention and Postvention to Suicide (NEPPS) in the city of João Pessoa. These reports dealt with the conditions of suicide production, the process of death (disincarnation) and the experience after death. For the analysis of the reports, we took the fundamentals of discourse analysis in the vision of Michel Foucault as basic theoretical framework. We mobilized, among other discursive objects, Retextualization (MARCUSCHI 2003); The psychological Autopsy, (GUEVARA 2001, 2006), the notion of person in the field of Anthropology (MAUSS, 1974) and of Spiritism. We also used the objects health, care and the suicide and the suicidal by the optics of the medical domain (WHO) and the religious system of Spiritism as well. Thus, this is a qualitative research carried out in the field that used as data collection instruments the participant observation and the life story (NOGUEIRA, 2017; BARROS, 2004, 2007) conveyed through autobiographical reports. As result, we identified that the suicidal spirits produce a discourse whereby they convey meanings about discursive objects such as suffering, disappointment, repentance, remorse, immortality, rescue of the suicidal, spiritual treatment and exhortation to life; The speech that confirmed the aforementioned hypothesis. We hope that this research may contribute to responses to demands imposed by the suicide problem. Keywords: Suicide. Prevention. Care. Spiritism. Suicidal spirit.